2009
DOI: 10.1007/s10705-009-9290-7
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization effects on yield sustainability and soil properties under irrigated wheat–soybean rotation of an Indian Himalayan upper valley

Abstract: To date, the sustainability of wheat (Triticum aestivum)-soybean (Glycine max) cropping systems has not been well assessed, especially under Indian Himalayas. Research was conducted in 1995-1996 to 2004 at Hawalbagh, India to study the effects of fertilization on yield sustainability of irrigated wheat-soybean system and on selected soil properties. The mean wheat yield under NPK ? FYM (farmyard manure) treated plots was *27% higher than NPK (2.4 Mg ha -1 ). The residual effect of NPK ? FYM caused *14% increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 36 publications
2
10
0
1
Order By: Relevance
“…To isolate the overall impact of treatments in terms of comparable yield data, the yield of maize was converted into wheat equivalent yield (WEY) following Bhattacharyya et al (2010). The converted maize yield of a year was then added to the actual yield of wheat in that year.…”
Section: Calculation Of Wheat Equivalent Yieldmentioning
confidence: 99%
“…To isolate the overall impact of treatments in terms of comparable yield data, the yield of maize was converted into wheat equivalent yield (WEY) following Bhattacharyya et al (2010). The converted maize yield of a year was then added to the actual yield of wheat in that year.…”
Section: Calculation Of Wheat Equivalent Yieldmentioning
confidence: 99%
“…Bhattacharyya et al (2008) observed reduced annual yield of a soybean-wheat rotation system when only mineral fertilizers were applied, in comparison with the bovine farmyard manure use. In spite of the lower contribution of nutrients per volume, organic amendments, such as bovine manure and poultry litter might even be superior to the mineral fertilizers, improving the biological, physical and chemical attributes of the soil (Bhattacharyya et al, 2010). Evaluating the effects of several applications of organic wastes, such as the turkey litter, over the years, Pinto et al (2012) found improving on soil fertility, increasing the pH, N, P, K, and base saturation rates, as well as organic carbon, and decreasing aluminum saturation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Bhattacharyya et al (2010) conducted a field experiment at an Indian Himalayan upper valley and reported that the wheat yield under NPK+FYM was 27% higher than NPK and the residual effect of NPK+FYM to the succeeding soybean crop increased soybean yield by 14% compared to NPK alone. Soils under NPK + FYM contained higher soil organic C, total soil N, total P and Olsen‐P by 10, 42, 52, and 71%, respectively, compared with NPK only.…”
mentioning
confidence: 99%